Clinical Case 07—Acute myocardial infarction due to paradoxical embolism: a difficult and underrecognized diagnosis. (21st October 2022) - Oliveira, Cátia; Proença, Tânia; Pinho, Ana; Santos, Luís; Cabrita, André; Marques, Catarina; Amador, Ana Filipa; Calvão, João; Costa, Catarina; Carvalho, Miguel; Pinto, Ricardo; Lebreiro, Ana; et al.
Abstract: Paradoxical embolism occurs when embolic material crosses from the venous to the arterial circulation through an intracardiac defect, such as a patent foramen ovale (PFO). Although rare, it may be a cause of acute coronary syndrome (ACS), requiring a high degree of clinical suspicion for diagnosis. We report a case of a 30-year-old man presenting in the emergency department with prolonged atypical left thoracic pain, electrocardiogram showing sinus rhythm with 1 mm ST-elevation in the inferior leads, and high-sensitivity troponin I elevation (maximum of 20 682 ng/L). The patient underwent emergent coronary angiography which showed apparently normal coronary arteries. The patient was then submitted to cardiac magnetic resonance that showed a recent transmural infarction of the inferior wall. ( Figure 1 ). A right coronary branch was assumed as the culprit. Additional study was made, with trans-esophageal echocardiogram (TEE) with agitated saline test revealing a PFO with spontaneous right-left shunt ( Figure 1 ). No intra-cavitary thrombus or other embolic source were found and the patient remained in sinus rhythm. Thrombophilia and auto-immune panel were negative. A presumptive diagnosis of paradoxical coronary emboli was made. PFO closure was performed with the Noblestich© system (a suture-based system). In conclusion, although paradoxical coronary artery embolism is an established cause of ACS, it requires a high degree of clinical suspicion for diagnosis. Recognition of this condition is important as it influences patients' management and prognosis and percutaneous device closure of the PFO should be considered to prevent future embolic events. Figure 1 A: Short axis cardiac resonance showing transmural late gadolinium enhancement in the inferior wall. B and C: Trans-esophageal echocardiography with Doppler signal (B) and agitated saline test (C) showing the PFO with shunting.